Cloning, characterization and expression of the gene that encodes the major neutralization-specific antigen of African horsesickness virus serotype 3. - Vreede, F; Huismans, H (1994)
The gene encoding the outer capsid protein, VP2, of African horsesickness virus serotype 3 (AHSV-3) has been sequenced in its entirety from cDNA clones of the segment 2 RNA, and compared with the previously published VP2 gene sequence of AHSV-4. AHSV-3 genome segment 2 was shown to be 3221 nucleotides in length, encoding a protein of 1057 amino acids with a 50.5% identity to the amino acid sequence of AHSV-4 VP2. Two areas of high variability (approximately 35% identity) were identified. The N-proximal variable region (amino acids 128 to 309) exhibited significant hydrophilicity, suggesting a possible role in the determination of the serotype-specific immune response. VP2 of AHSV-3 has furthermore been expressed in a baculovirus expression system. The expressed protein was shown to react specifically with an anti-AHSV-3 serum in Western blots. Antibodies raised in rabbits and guinea-pigs against the recombinant VP2 neutralized the virus in a plaque reduction assay, confirming the identity of VP2 as the major neutralization-specific antigen of AHSV.